Wishin' and hopin' [compact disc, unabridged] : a Christmas story - Lamb, Wally (Harperaudio, 2009)
It's 1964 and ten-year-old Felix is sure of a few things: the birds and the bees are puzzling, television is magical, and this is one Christmas he'll never forget.